Implementasi VoIP Sebagai Media Komunikasi pada Dinas Perhubungan Komunikasi Informasi dan Telematika Aceh - Syafrinal Syafrinal (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2019)
The purpose of this study is to design and build voice communication over IP networks using the Briker operating system. The use of VoIP Server to make calls from VoIP clients to fellow VoIP clients, and from people's VoIP numbers to one of the VoIP clients, and also looking for a comparison of public IP client and local IP voice delay at Dishubkomintel Aceh. The research method consisted of several stages namely; 1) System Design, 2) Network Topology, 3) Server-Side Design, 4) Client-Side Design, 5) Operating System and Application Installation, 6) Configuration, 7) VoIP Network Connectivity Testing, and 8) VoIP Work Observation. From the test results, several conclusions can be drawn namely; 1) VoIP Server Briker has a role in handling SIP calls from all registered clients into the Briker Server, 2) Between VoIP clients can communicate two ways with each other when registered into the Briker Server, 3) Calls to public VoIP are made by pressing '9' which used as Outbound routes then continued by pressing the destination number, and 4) Calls from VoIP of the people to VoIP are made by pressing the VoIP phone number of the people connected to the VoIP Server and then received by VRR (Voice Response Response) which will be directed to the extension number headed.